2014
DOI: 10.1021/ie403967z
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Characterization of Heavy Petroleum Fluids Using Group Contribution Methods

Abstract: Application of an approach recently published [Carreoń-Calderoń et al. Ind. Eng. Chem. Res. 2012, 51, 14188− 14198] to heavy petroleum fluids allows calculation of critical properties and molecular pseudostructures of their undefined fractions. This approach is based on group contribution methods, where classical thermodynamics is used as framework to assign functional groups to each undefined fraction by minimizing its free energy. The calculated properties are employed to determine parameters entering into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Previous authors focused mostly on petrochemical systems [7][8][9][10][11][12][13][14] and wood tars 15 and applied a pseudo-component approach. This differs substantially from the NEAT approach, which aims at predicting a property of a single target component using a group contribution method.…”
mentioning
confidence: 99%
“…Previous authors focused mostly on petrochemical systems [7][8][9][10][11][12][13][14] and wood tars 15 and applied a pseudo-component approach. This differs substantially from the NEAT approach, which aims at predicting a property of a single target component using a group contribution method.…”
mentioning
confidence: 99%
“…Carreón-Calderón et al (2012 have suggested two group contribution methods; Joback-Reid (JR) (Joback and Reid, 1987) and Marrero-Gani (MG) (Marrero and Gani, 2001). JR method was suggested to simulate VLE of light petroleum fluids (Uribe-Vargas et al, 2016), while MG method showed better functionality in heavy petroleum fluids heavier than 14 API (Carreón-Calderón et al, 2014). In the latter, the C 7+ fraction, which has unknown composition, was split in 3, 6 and 9 pseudocomponents, founding no significant difference between calculations and experiments regardless of the fraction splitting.…”
Section: Characterization Proceduresmentioning
confidence: 99%
“…They used selected functional groups to assign a hypothetical chemical structure to an undefined petroleum fraction by a minimization process of its corresponding Gibbs free energy. This methodology was applied to simulate VLE of heavy (Carreón-Calderón et al, 2014) and light hydrocarbons (Uribe-Vargas et al, 2016). Good results were achieved in both cases without making use of correlations to calculate critical properties or adjusted binary interaction parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Research of the GCM keeps attracting increasing attention in these years. The applications of the GCM have extended to the determination of thermal conductivity of liquid chemicals 20 , the prediction of enthalpy of fusion of pure compounds 21 , the radiative efficiency estimation of organic substance 22 , as well as the fields of heavy petroleum fluids 23 , vegetable oils, and biodiesel 24 . Moreover, a great part of the recent researches on the GCM focuses on the applications of ionic liquids [25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%